New Virgulid Cercaria (Trematoda, Lecithodendroidea) from the Mollusk Melanopsis praemorsa (Melanopsidae) from Azerbaijan Water Bodies. Morphology and Chaetotaxy of Cercaria agstaphensis 11 - Manafov, A.A. (Вестник зоологии, 2011)
An illustrated morphological description with chaetotaxy and differential diagnosis of the new form of virgulid cercaria – Cercaria agstaphensis 11 from freshwater prosobranchial mollusks Melanopsis praemorsa (Linnaeus, 1758) are given. Special attention is paid to the tegument armament, the structure of glandular apparatus, excretory system, digestive system, the structure of the sensory apparatus and other larval morphological characters. Приведены рисунки, описание морфологии, в том числе и хетотаксии, а также дифференциальный диагноз новой виргулидной церкарии – Cercaria agstaphensis 11 из пресноводного переднежаберного моллюска Melanopsis praemorsa (Linnaeus, 1758). Особое внимание уделено вооружению тегумента, строению железистого аппарата, экскреторной системы, пищеварительной системы, строению сенсорного аппарата и других морфологических особенностей строения личинок.